2001
DOI: 10.1042/cs1010671
|View full text |Cite|
|
Sign up to set email alerts
|

The UKPDS risk engine: a model for the risk of coronary heart disease in Type II diabetes (UKPDS 56)

Abstract: A definitive model for predicting absolute risk of coronary heart disease (CHD) in male and female people with Type II diabetes is not yet available. This paper provides an equation for estimating the risk of new CHD events in people with Type II diabetes, based on data from 4540 U.K. Prospective Diabetes Study male and female patients. Unlike previously published risk equations, the model is diabetes-specific and incorporates glycaemia, systolic blood pressure and lipid levels as risk factors, in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
588
4
19

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 789 publications
(620 citation statements)
references
References 17 publications
9
588
4
19
Order By: Relevance
“…We have previously shown that meta-analyses of HbA 1c and diabetic complications, including several studies based on baseline HbA 1c , led to underestimations of the pooled risk [1,26]. We have also shown that the use of updated mean HbA 1c which does not consider the prolonged effect of HbA 1c , probably leads to substantial underestimations of the predictive ability of HbA 1c , a finding that is important in health economical analyses and risk engines [2,27]. We now confirm those results and further support those conclusions, and now it would be important to carry out analyses corresponding to those presented here for other diabetic complications.…”
Section: Discussionmentioning
confidence: 94%
“…We have previously shown that meta-analyses of HbA 1c and diabetic complications, including several studies based on baseline HbA 1c , led to underestimations of the pooled risk [1,26]. We have also shown that the use of updated mean HbA 1c which does not consider the prolonged effect of HbA 1c , probably leads to substantial underestimations of the predictive ability of HbA 1c , a finding that is important in health economical analyses and risk engines [2,27]. We now confirm those results and further support those conclusions, and now it would be important to carry out analyses corresponding to those presented here for other diabetic complications.…”
Section: Discussionmentioning
confidence: 94%
“…The 10 year UK Prospective Diabetes Study (UKPDS) CHD/stroke risk engine scores were calculated in all patients at baseline and after 30 and 90 days [6].…”
Section: Methodsmentioning
confidence: 99%
“…213 The regression dilution ratio method is exact for linear models and has been shown to apply approximately to other generalised linear models. 212 It can be shown that it applies approximately in the case of univariate survival models with censoring.…”
Section: Repeated Lipid Measuresmentioning
confidence: 99%
“…It follows that if the variability of the measure is to be reduced, for example by taking an average, the coefficient in the risk score must be increased. 213 Here we use the results of Chapter 2 to estimate the modifications necessary to use CVD risk calculators with the mean of three and five lipid measurements.…”
Section: Introductionmentioning
confidence: 99%